Affect, race, and white discomfort in schooling: decolonial strategies for 'pedagogies of discomfort' - Zembylas, Michalinos (Ethics and education, 2018)
The present paper theorises white discomfort as not an individual psychologised emotion, but rather as a social and political affect that is part of the production and maintenance of white colonial structures and practices. Therefore, it is suggested that white discomfort cannot be critically addressed merely in pedagogic terms and conditions within schools and universities. By foregrounding white discomfort in broader terms, the aim of the paper is to provide a more holistic and dynamic account which opens up a realm that situates the pedagogisation of white discomfort within the broader decolonising project of disrupting white colonial structures and practices. The paper calls for both a decolonising and a critical affective approach to pedagogies of discomfort that would focus on examining and addressing strategically how white discomfort comes to be experienced and dismantled within broader affective, material and discursive assemblages of race, racism and whiteness.